ENVIRONMENTAL IMPACT ASSESSMENT (EIA)-DECISION MAKING TOOL FORPROJECT APPROVAL IN INDIA - Pratibha, Akhand; Sonal, Navlkha; Archna, Akhand (International Journal of Research -GRANTHAALAYAH, 2015)
Environmental Impact Assessment (EIA) can broadly be defined as a study of the effects of a proposed project, plan or program on the environment. A Strength, Weakness and Opportunity analysis taken up in this article has suggested that there are several issues that need to be readdressed. The opportunities are realized as increasing public awareness, initiatives of environmental groups and forward thinking to environmental plans and policies. Poor governance, rapid economic reforms and favors to small - scale units are threats the system. This paper concludes with EIA procedure in India.